2020
DOI: 10.1155/2020/9371426
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Active Constituents and Optimal Steaming Conditions Related to the Hematopoietic Effect of Steamed Panax notoginseng by Network Pharmacology Coupled with Response Surface Methodology

Abstract: During hundreds of years of medication, it is believed that the steamed Panax notoginseng (SPN) can enrich and regulate the blood, replenish the body, and improve the health. The aim of this study was to optimize the steaming conditions of SPN which are related to the hematopoietic effect. In the study, network pharmacology and pharmacological experiments were used to predict and verify the potential hematopoietic active ingredients of SPN. Three variables including the steaming time (2-10 h), steaming tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…In Cytoscape, we used the plug-in cytoNCA to calculate the value of degree centrality (DC) and closeness centrality (CC) of all nodes in the network. As a standard for filtering ingredients and targets, we considered the nodes with values greater than the median value of DC and CC as the key nodes in our network [ 23 ]. Based on the new network, we can intuitively identify relationships between TXYF's active ingredients and its target targets.…”
Section: Methodsmentioning
confidence: 99%
“…In Cytoscape, we used the plug-in cytoNCA to calculate the value of degree centrality (DC) and closeness centrality (CC) of all nodes in the network. As a standard for filtering ingredients and targets, we considered the nodes with values greater than the median value of DC and CC as the key nodes in our network [ 23 ]. Based on the new network, we can intuitively identify relationships between TXYF's active ingredients and its target targets.…”
Section: Methodsmentioning
confidence: 99%
“…Network pharmacology is a novel and efective method to systematically and comprehensively describe the law of interactions between components and targets through the integration of chemoinformatics, bioinformatics, network biology, network analysis, and traditional pharmacology [24,25]. Recently, network pharmacology has been successfully employed to investigate the active compounds and the underlying mechanism of TCM with complex chemical composition [26][27][28][29][30]. Molecular docking simulation is an important way of drug virtual screening, which can provide useful information about drug-receptor interactions by calculating the binding energy of small-molecule ligands (drugs) with proteins (receptors) [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, RPN can remove blood stasis and arrest bleeding, while SPN has a restorative effect for its nourishing function and blood cell-increasing (Zhou et al. 2020 ). Prevailing studies confirmed that the RPN displayed high potency for haemostasis, analgesic effects, anticoagulant, anti-inflammatory, while the SPN has better antitumor, antioxidation, antiaplastic anaemia and enhances immune function activities (Lau et al.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological effects of P. notoginseng change during the steaming process and there is a description for P. notoginseng medicinal properties that 'the raw products eliminate and the steamed forms tonify' (Wu et al 2018). That is to say, RPN can remove blood stasis and arrest bleeding, while SPN has a restorative effect for its nourishing function and blood cell-increasing (Zhou et al 2020). Prevailing studies confirmed that the RPN displayed high potency for haemostasis, analgesic effects, anticoagulant, anti-inflammatory, while the SPN has better antitumor, antioxidation, antiaplastic anaemia and enhances immune function activities (Lau et al 2009;Li et al 2011;Chen et al 2013;Wu et al 2014;Wei et al 2018;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%